Undergraduate Students’ Reading Choices in the University of Benin, Nigeria - Olemekwu Aika, Patience Ihianakuihiomen; Ofuani, Felicia Ngozi (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024, 2024)
This study examined the reading choices and time spent reading of undergraduate students in the University of Benin, Nigeria. One research question and three hypotheses gave direction to the work. The study utilized the descriptive survey research design, using a questionnaire as the research instrument. A sample of 326 students were conveniently selected from four faculties and across four academic levels. Findings revealed that students generally preferred the reading of journals, newspapers, textbooks and magazines in descending order. However, comic books, non-fiction and fiction were materials less frequently read. Similarly, the amount of time students spend reading is inadequate to meet their academic and leisure reading needs. In addition, students’ reading choices did not differ by sex. However, significant differences were found in students’ reading choices by academic levels. It was recommended among other that undergraduate students should be encouraged to devote more time to reading and to read a variety of materials. Keywords: Undergraduate reading, reading choices, Reading time, Leisure reading, Academic level